A BAFF/APRIL-dependent TLR3-stimulated pathway enhances the capacity of rheumatoid synovial fibroblasts to induce AID expression and Ig class-switching in B cells. Issue 10 (27th July 2011) - Bombardieri, Michele; Kam, Ngar-Woon; Brentano, Fabia; Choi, Ken; Filer, Andrew; Kyburz, Diego; McInnes, Iain B; Gay, Steffen; Buckley, Christopher; Pitzalis, Costantino
Abstract : Objectives: To dissect the role of toll-like receptor (TLR) signalling and B cell survival/proliferating factors in the crosstalk between rheumatoid arthritis synovial fibroblasts (RASF) and B cells. Methods: RASF, rheumatoid arthritis dermal fibroblasts (RADF) and osteoarthritis synovial fibroblasts (OASF) were analysed for the expression of B cell survival/proliferating factors BAFF and APRIL in resting conditions and upon stimulation with TLR2/TLR3/TLR4 ligands. Unswitched IgD+ B cells were co-cultured with RASF/OASF/RADF in the presence/absence of TLR ligands and with/without BAFF/APRIL blocking antibodies. Activation-induced cytidine deaminase (AID) mRNA expression, Iγ-Cμ and Iα-Cμ circular transcripts (CTs; markers of ongoing class-switching to IgG and IgA) and IgM/A/G production were measured to assess functional activation of B cells. Results: TLR3 and to a lesser extent TLR4, but not TLR2 stimulation, induced up to ∼1000-fold BAFF mRNA and increased soluble BAFF release. APRIL was less significantly regulated by TLR3. Resting and TLR3-stimulated RASF released higher levels of BAFF/APRIL compared with RADF. TLR3 stimulation of RASF but not RADF in co-culture with B cells strongly enhanced AID expression, Iγ-Cμ and Iα-Cμ CTs and class-switching to IgG/IgA. Blockade of BAFF/APRIL signalling completely inhibited TLR3-induced, RASF-dependent expression of AID, CTs and the secretion of IgG/IgA. Conclusions: RASF produce high levels of BAFF and APRIL constitutively and in response to TLR3 stimulation. These factors are critical in directly modulating AID expression, class-switch recombination and IgG/IgA production in IgD+ B cells. Overall, this work highlights a novel and fundamental role for the TLR3/B cell survival factor axis in sustaining B cell activation in the rheumatoid arthritis synovium.